2011
DOI: 10.1002/pssr.201105014
|View full text |Cite
|
Sign up to set email alerts
|

EPR spectroscopy of weak exchange interactions between Co2+ ions in ZnO

Abstract: Electron paramagnetic resonance (EPR) is used to identify the next nearest neighbour Co2+ pairs coupled by spin–spin interaction in Co‐doped ZnO single crystals grown by the hydrothermal technique. These dimer centers are described by a spin Hamiltonian with exchange coupling terms written as interaction between identical effective spins Seff = 1/2 of the lowest ground state Kramers doublets of the two Co2+ ions. The exchange parameters of weakly ferromagnetically coupled next nearest neighbor Co2+ pairs are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…Spectrum of Co 2+ ions (3d 7 configuration) was described by spin Hamiltonian for electron spin S = 3/2: H=βB·g·S+Dtrue[Sz213Sfalse(S+1false)true]+bold-italicS·bold-italicA·bold-italicI, where β is Bohr magneton, g || = 2.24, g ⊥ = 4.554, and A || = 15.9 × 10 −4 cm −1 , A ⊥ = 2.89 × 10 −4 cm −1 are the hyperfine interaction constants of 59 Co isotope (100%) with I = 7/2 . We have not observed Co 2+ ion pairs, as reported in or Cu 2+ ions in ESR spectra.…”
Section: Methodssupporting
confidence: 61%
See 1 more Smart Citation
“…Spectrum of Co 2+ ions (3d 7 configuration) was described by spin Hamiltonian for electron spin S = 3/2: H=βB·g·S+Dtrue[Sz213Sfalse(S+1false)true]+bold-italicS·bold-italicA·bold-italicI, where β is Bohr magneton, g || = 2.24, g ⊥ = 4.554, and A || = 15.9 × 10 −4 cm −1 , A ⊥ = 2.89 × 10 −4 cm −1 are the hyperfine interaction constants of 59 Co isotope (100%) with I = 7/2 . We have not observed Co 2+ ion pairs, as reported in or Cu 2+ ions in ESR spectra.…”
Section: Methodssupporting
confidence: 61%
“…Different types of magnetic resonance (MR) signals of ZnCoO were reported in the literature. For samples with a low Co fraction ESR signals of isolated Co 2+ ions and Co–Co pairs were detected, showing the characteristic hyperfine structure of Co . For ZnCoO layers with 10% Co concentration Jedrecy et al observed a broadened and anisotropic paramagnetic signal related to substituting Co 2+ ions.…”
Section: Discussionmentioning
confidence: 99%
“…This was explained by invoking the mechanism involving additional defects, e.g. singly charged oxygen vacancies [38]. Another possibility for the existence of ferromagnetically coupled Co 2?…”
Section: Origin Of Ferromagnetism In Oxide Nanoparticlesmentioning
confidence: 99%
“…This was explained by invoking the mechanism involving additional defects, e.g. singly charged oxygen vacancies [25]. Another possibility for the existence of ferromagnetically coupled Co 2 þ ions in this nanoparticles was pointed out in [6], where the competition of two Co ions population occurred: one with antiferromagnetic interaction between Co ions and the other with ferromagnetic interaction.…”
Section: Ferromagnetismmentioning
confidence: 98%
“…Co 2 þ -doped ZnO nanoparticles are prospective DMS candidates, and have been investigated extensively . EPR studies of the Co 2 þ ion in magnetic semiconductors, such as SnO 2 [26], provide information on the magnetic state of this compound, and its behavior under different synthesis conditions [1,[16][17][18][19][20][21][22][23][24][25]. The main conclusions of these investigations are: (i) there are present both localized Co 2 þ ions and ferromagnetically coupled Co 2 þ ions in the host material; (ii) The spin-Hamiltonian (SH) parameters for the Co 2 þ ion are very close to those for Co 2 þ -substituted ZnO crystal, characterized by highspin Co 2 þ ions; (iii) there is exhibited an electron paramagnetic resonance (EPR) signal due to Co 2 þ ions, situated in distorted local environment, characterized by high-spin Co 2 þ ions.…”
Section: Introductionmentioning
confidence: 99%